Towards agile talent management: the opportunities of a skills-first approach - Jooss, Stefan; Collings, David; McMackin, John Francis; Dickmann, Michael (Academy of Management, 2023)
Despite its evolution over the last two decades, talent management has been criticised for being too static in its approach. Drawing on matching theory and adopting an agility lens, we show how a skills-matching perspective on talent management fosters the development of strategic agility, responsive to external and internal demands. Through qualitative research encompassing 34 interviews in 15 multinational enterprises, we illustrate how a skills focus required revisiting talent strategies to facilitate initial and dynamic matching in external and internal labour markets, and we highlight key boundary conditions for skills-matching. We reveal a set of dynamic capabilities, underlying two meta-capabilities, strategic sensitivity and resource fluidity, which underpin the skills-matching process and enable strategic agility. In doing so, we shift the focus of talent management towards skills acquisition and development, and emphasise the need to look beyond traditional learning and development to alignment across the wider talent function.
Keywords: Talent management; skills; matching theory; agility; dynamic capabilities